Randomized Pilot Trial of Intensive Management of Blood Pressure or Volume Expansion in Subarachnoid Hemorrhage (IMPROVES). Issue 2 (29th December 2014) - Togashi, Kei; Joffe, Aaron M.; Sekhar, Laligam; Kim, Louis; Lam, Arthur; Yanez, David; Broeckel-Elrod, Jo Ann; Moore, Anne; Deem, Steve; Khandelwal, Nita; Souter, Michael J.; Treggiari, Miriam M.
ABSTRACT: BACKGROUND: Volume expansion and hypertension are widely used for the hemodynamic management of patients with subarachnoid hemorrhage. OBJECTIVE: To investigate the feasibility, adherence, and retention in a trial of volume expansion and blood pressure manipulation to prevent delayed cerebral ischemia. METHODS: A randomized pilot trial using a 2-way factorial design allocating patients within 72 hours of subarachnoid hemorrhage to either normovolemia (NV) or volume expansion (HV) and simultaneously to conventional (CBP) or augmented blood pressure (ABP) for 10 days. The study endpoints were protocol adherence and retention to follow-up. The quality of endpoints for a larger trial were 6-month modified Rankin Scale score, comprehensive neurobehavioral assessment, delayed cerebral ischemia, new stroke, and discharge disposition. RESULTS: Twenty patients were randomized and completed follow-up. The overall difference in daily mean intravenous fluid intake was 2099 mL (95% confidence interval [CI]: 867, 3333), HV vs NV group. The overall mean systolic blood pressure difference was 5 mm Hg (95% CI: −4.65, 14.75), ABP vs CBP group. Adverse events included death (n = 1), delayed cerebral ischemia (n = 1), and pulmonary complications (n = 3). There were no differences in modified Rankin Scale score between HV and NV (difference 0.1; 95% CI: −1.26, 1.46, P = .87) or between ABP and CBP groups (−0.5, 95% CI: −1.78, 0.78, P = .43). Neuropsychological scores were similar between HV vs NV, but tended to be worse in ABP (57 ± 27) vs CBP group (85 ± 21, P = .04). CONCLUSION: This pilot study showed adequate feasibility and excellent retention to follow-up. Given the suggestion of possible worse neurobehavioral outcome with ABP, a larger trial to determine the optimal blood pressure management in this patient population is warranted. (ClinTrials.gov NCT01414894.)